Paravertebral Anaesthesia In Goats Using Bupivacaine Hydrochloride - John Martin KD (Department of Surgery, College of Veterinary and Animal Sciences, 1994)
The study was conducted in 15 apparently healthy Alpine – Malabari crossbred male goats of 9 to 12 months of age. Three goats were embalmed and used for dissection studies and the remaining 12 goats were used for nerve blocking trials, repeatedly at 10 days interval. The study was conducted in three parts. Part 1: Distribution of thoracic and lumbar spinal nerves in the abdominal region The origin, course and distribution of the 10th thoracic to the third lumbar spinal nerves were studied on both flank. The spinal nerves emerged through the intervertebral foramina, and divided into dorsal and ventral primary branches. The dorsal primary branch released the dorsomedial branch and continued as the dorsolateral branch. The former ramified into the multifidus dorsi and longissimus dorsi muscles and the latter ramified into the cutaneous truncimuscle and skin of the upper third of the body wall. The dorsolateral branch of the 10th, 11th and 12th thoracic spinal nerves supplied the serratus dorsalis caudalis muscles and the thoracolumbar fascia in their course. The ventral primary branch of the 10th, 11th and 12th thoracic spinal nerves gave away a ventrolateral branch which supplied the intercostal muscles, the origin of obliguus abdominis externus muscle and provided cutaneous innervation to the middle third of chest wall. The ventromedial branch terminated as fine branches between the transverse abdominis and rectus abdominis muscles, penetrated through the rectus abdominis muscle and the aponeuroses and supplied the skin on the ventral third of the chest wall. The ventral primary branches of the 13th thoracic, first and second lumbar spinal nerves coursed below the intertransversalis muscles, released ventrolateral branch and continued as the ventromedial branch. The former supplied the oblique muscles of abdomen and ramified into the skin and cutaneous muscles in the middle third of the flank. The latter terminated as fine branches, penetrated through the rectus abdominis muscle and the aponeuroses and formed the cutaneous innervation to the ventral abdominal wall. The ventral primary branch of the first and second lumbar spinal nerves have communicating branch, which traversed below the second lumbar transverse process. The ventral primary branch of the second lumbar spinal nerve gave away a small branch which ran caudad, below the lumbar transverse processes. The ventral primary branch of the third lumbar spinal nerve coursed back, below the lumbar transverse processes, between the psoas muscles. The lateral thoracic nerve of the brachial plexus supplied muscles on the ventral part of chest and abdomen and the cranial preputial muscle. One site (proximal site) was found suitable for blocking the 10th, 11th and 12th thoracic spinal nerves, while, two sites, proximal and distal, were found suitable for 13th thoracic, first, second and third lumbar spinal nerves. Part 11: The area desensitized by blocking individual spinal nerves supplying the flank region The 10th thoracic to the third lumbar spinal nerves were blocked individually in three different animals using 0.5 per cent bupivacaine hydrochloride solution and the area of analgesia was mapped. The 10th, 11th and 12th thoracic spinal nerves were blocked at the proximal site. The area of analgesia was similar, with S – shape, commencing from the dorsal midline to a point between the costal arch and the ventral midline. The 13th thoracic, first second and third lumbar spinal nerves were blocked at two sites, viz., Proximal site : The area of analgesia for the 13th thoracic, first and second lumbar spinal nerves commenced from the dorsal midline, and terminated lateral to the ventral midline. The area of analgesia of the third lumbar spinal nerve extended over the caudodorsal part of the flank. Distal site: The results of the study for each of the spinal nerves were inconsistent. Based on this study, it was concluded that, for anaesthetizing the flank, the 13th thoracic, first and second lumbar spinal nerves are to be blocked simultaneously, at the proximal site. Part 111: Anaesthesia of the flank The 13th thoracic, first and second lumbar spinal nerves were blocked simultaneously at the proximal site, in two groups (A and B) of six goats each using 0.5 per cent and 0.25 per cent solutions of bupivacaine hydrochloride respectively. The time for onset of analgesia was 2.83 + 0.87 min. in subgroup A and 2.67 + 0.21 min. in subgroup B. The duration of analgesia was 215.83 + 14.97 min. and 105.67 + 31.13 min. in subgroups A and B respectively. The extent of analgesia obtained in all the trials in both of the subgroups were similar. It extended over the entire flank from dorsal midline to the ventral midline, except : (a) a triangular area at the anterodorsal angle of flank (b) the posteriodorsal corner of the flank, in front of the external angle of ilium and (C) the preputial orifice and the skin around it. The rectal temperature, heart rate, rate of respiration, and the rate of rumen motility did not show significant variation throughout the experiment in both the subgroups. Laparotomy was conducted in two animals from each subgroup. Analgesia was satisfactory over the skin, muscles and peritoneum and muscle relaxation was adequate. In addition, the following symptoms were observed a. Scoliosis at the lumbar region towards the side of nerve block b. bulging of the anaesthetized flank and c. difficulty in bearing weight on the hind limb on the side of nerve block, with knuckling on progression. One animal (No. A6) developed symptoms of toxicity viz., lateral recumbency, dialatation of pupil, champing of jaw, frothy salivation,severe clonic convulsions of neck and limb muscles and paddling movements. The animal had a spontaneous recovery.